2017
DOI: 10.21098/bemp.v20i2.810
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Stochastic General Equilibrium (Dsge) Model to Assess the Impact of Structural Reforms on the Indonesian Economy

Abstract: One of the Government programs to spur economic growth is to improve the availability andquality of infrastructure through increased government spending on infrastructure development. In this paper, we build a DSGE model for a small open economy to predict the impact of government spending on output and welfare in Indonesia. The DSGE model uses parameters in line with the characteristics of Indonesian economy. The simulation results show that in the short run a 1% increase in government spending on consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Therefore, the impact of local government intervention in the land market on resource allocation is not only reflected in the allocation of land resources but also its impact on the allocation of capital and labor factors cannot be ignored. Undoubtedly, existing studies suggested that there are other determinants that can also play a decisive role in the growth of TFP such as foreign investment (Mankiw et al, 1992;Umar, 2017), the input in funds for scientific and technological endeavors (Zhou et al, 2019), and government intervention (Sahminan et al, 2017). The policy of LTM is still one of the important factors shaping the green TFP through multiple channels, especially its impacts on the status of resource allocation.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…Therefore, the impact of local government intervention in the land market on resource allocation is not only reflected in the allocation of land resources but also its impact on the allocation of capital and labor factors cannot be ignored. Undoubtedly, existing studies suggested that there are other determinants that can also play a decisive role in the growth of TFP such as foreign investment (Mankiw et al, 1992;Umar, 2017), the input in funds for scientific and technological endeavors (Zhou et al, 2019), and government intervention (Sahminan et al, 2017). The policy of LTM is still one of the important factors shaping the green TFP through multiple channels, especially its impacts on the status of resource allocation.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…Second, regarding the NK-DSGE model, there are various papers estimating this model for policy analysis in the developing and emerging economies [Liu and Zhang (2010), Gu et al (2014) and Dai et al (2015) for China; Elekdag et al (2005) and Choi and Hur (2015) for Korea; Sahminan et al (2017) and Gu et al (2014) for Indonesia; Ramayandi (2011) for four ASEAN countries such as Malaysia, Thailand, Indonesia and Philippines; Saxegaard et al (2010) and Gabriel et al (2016) for India; Silveira (2008) and Palma and Portugal (2014) for Brazil, Castillo et al (2013) for Peru, Medina and Soto (2007) for Chile and Steinbach et al (2009) for South Africa].…”
Section: Business Cycle Fluctuations In Vietnammentioning
confidence: 99%
“…Not surprisingly, there is a growing list of recent studies on calibrating and estimating DSGE models for Indonesia to analyze various issues: among others, , Alamsyah (2004), Tjahjono and Waluyo (2010), Harmanta et al (2013Harmanta et al ( ), (2014, Dutu (2016), and Sahminan et al (2017). Interests on this literature have been ramped up by Bank Indonesia's (and to some extent, the Ministry of Finance's) increasing need for a good-fitting and reliable DSGE model to be used for forecasting and policy simulations.…”
Section: Related Literature and Contributionmentioning
confidence: 99%
“…Interests on this literature have been ramped up by Bank Indonesia's (and to some extent, the Ministry of Finance's) increasing need for a good-fitting and reliable DSGE model to be used for forecasting and policy simulations. Not surprisingly, there is a growing list of recent studies on calibrating and estimating DSGE models for Indonesia to analyze various issues: among others, , Alamsyah (2004), Tjahjono and Waluyo (2010), Harmanta et al (2013), (2014), Dutu (2016), and Sahminan et al (2017). Aside from Dutu (2016), none of the existing studies considers inflation-target adjustmentsthey simply assume that the inflation target is constant.…”
Section: Related Literature and Contributionmentioning
confidence: 99%